Nominal diminutives in Slovene and English - Sicherl, Eva (Linguistica (Ljubljana), 2011)
This contrastive treatment of diminutives in Slovene and English aims to comment on the productivity of diminutive formations in both languages; in Slovene diminutives are particularly productive also in the field of terminology. Diminutiveness can be expressed in both languages in different ways: in Slovene lexemic word-formation is prevalent, while in English the same content is usually expressed syntactically. However, a combination of both is possible as well, as for example in hišica - majhna hiša - majhna hiška. A dual nature of diminutiveness can also be detected in graded cases like hiša - hiška - hiškica, hči - hčerka - hčerkica. In English the formation of diminutives is less productive, however, the expression of diminutiveness is thus transferred to the syntactic level and is, as such, limitless. Since Slovene is a highly morphemic language it is only natural that diminutiveness should be expressed morphemically. The aim of the article is to highlight some differences in the ways diminutiveness can be expressed in both languages by means of examples.
Keywords: anglais; angleščina; diminutifs; English; linguistique comparée; manjšalnice; noms diminutifs; primerjalno jezikoslovje; samostalniške manjšalnice; Slovene; slovenščina